Incidence and distribution of cassava mosaic begomoviruses in Cote d'Ivoire - Toualy, M.N.Y.; Akinbade, S.; Koutoua, S.; Diallo, H.; Kumar, P. Lava (2014)
Cassava mosaic disease (CMD) caused by the whitefly-transmitted begomoviruses (family Geminiviridae) is amajor threat to production of cassava (Manihot esculenta Crantz) in Côte d’Ivoire. A survey was conducted in themajor production zones in Côte d’Ivoire to assess the incidence, severity, and distribution of cassava viraldiseases. At each survey site, up to ten plants were assessed for symptom severity; incidence and samples weretaken for virus testing. Techniques based on polymerase chain reaction (PCR) were used for the detection ofcassava mosaic begomoviruses (CMBs) in the sampled leaves. Incidence of CMD varied from 0 to 100% andsymptom severity from 1 to 5. Incidence differed significantly between the various agro-ecological zones(P<0.001), but severity was the same in those zones. Out of the 335 samples tested, African cassava mosaic virus(ACMV) was detected in 43.3%, East African cassava mosaic Cameroon virus (EACMCV) in 5.7%, and bothACMV and EACMCV in 31.3%; 19.7% of the samples analyzed were negative to all the viruses tested. None of thesamples was tested positive to the East African cassava mosaic virus-Uganda (EACMV-Ug). These resultssuggest high incidence of CMD in the cassava production zones in Côte d’lvoire and underscores a need forimplementation of control measures including phytosanitary measures with utilization of CMD-free materials forplanting and adoption of resistant varieties.